1987
DOI: 10.1002/lipi.19870890706
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Composition of Some Convolvulaceae and Leguminosae Seeds and the Oils

Abstract: B y M . H . K i t t u r , C. S. M a h a j a n s h e t t i andG. L a k s h m i n a r a y a n a *The seeds of Quamoclit coccinea, Ipomma horsfalliae, Argyria aggregata, Merremia pentaphylla (Convolvulaceae), Indigofera hirsuta, Dalbergia mlanarylon and Bauhinia vahlii (Leguminosae) as well as the oils extracted therefrom were analysed for physico-chemical characteristics and composition. The oil content was appreciable in 9: coccinea (22.6 O h ) , I. horsfalliae (19.8 O/o),A. aggregata (13.5 "h) and D . mlanoxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Table 2 gives the fatty acid profiles of the six oils studied in the present work. Oil yields from Overall, the most prominent fatty acid in the fatty acid profiles of Fabaceae (Leguminosae) is linoleic acid, shown not only by the present data in Table 2 (exception Clitoria ternatea which in this study contains slightly more linolenic acid that linoleic acid) but also by data in previous literature on less common Leguminosae oils [5][6][7][8][9]. Exceptions to this observation of the more than 110 fatty acid profiles in the previous literature [5][6][7][8][9] include Bauhinia vahlii [8], Canavalia ensiformis [5], Cassia fruticose [7], Centrosema pubescens [6, see Table 1], Clitoria rubiginosa [7], Clitoria ternatea [7; see Table 1], Crotalaria juncea [9], Elephantorrhiza goetzii [5], Erythrina indica [5], Lonchocarpus capassa [5], Millettia bussei [7], Pongamia glabra [5], Pseudocadia zambesiaca [5], Pueraria phaseoloides [6; C18:3 most common], and Tephrosia purpurea [5].…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Table 2 gives the fatty acid profiles of the six oils studied in the present work. Oil yields from Overall, the most prominent fatty acid in the fatty acid profiles of Fabaceae (Leguminosae) is linoleic acid, shown not only by the present data in Table 2 (exception Clitoria ternatea which in this study contains slightly more linolenic acid that linoleic acid) but also by data in previous literature on less common Leguminosae oils [5][6][7][8][9]. Exceptions to this observation of the more than 110 fatty acid profiles in the previous literature [5][6][7][8][9] include Bauhinia vahlii [8], Canavalia ensiformis [5], Cassia fruticose [7], Centrosema pubescens [6, see Table 1], Clitoria rubiginosa [7], Clitoria ternatea [7; see Table 1], Crotalaria juncea [9], Elephantorrhiza goetzii [5], Erythrina indica [5], Lonchocarpus capassa [5], Millettia bussei [7], Pongamia glabra [5], Pseudocadia zambesiaca [5], Pueraria phaseoloides [6; C18:3 most common], and Tephrosia purpurea [5].…”
Section: Resultssupporting
confidence: 79%
“…Minor to moderate amounts of saturated long-chain fatty acids appear to be typical for many, if not most, Leguminosae species as can be deduced from compilations of previous fatty acid profile data [5][6][7][8][9]. Some notable examples include Erythrina indicum with 16 % 22:0 [5], Tetrapleura tetraptera 20 % 22:0, 8 % 24:0 [5], Sindora wallichii 12 % C24:0 [7], Parkia roxburghii, Myroxylon toluiferum, Psophocarpus palustris, Pterocarpus indicus each 9 % C22:0 [7], Crotalaria juncea with 7.4 % 22:0 and 5.2 % 24:0 [9; also see text above] and differing reports on Trachylobium verrucosum as 11 % 24:0 [5] and 7 % C22:0 and 9 % C24:0 [7].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…While no information on the fatty acid profile on the seed oil of I. pes-caprae appears to be available in the literature, such data have been reported for various other Ipomoea species [4,[11][12][13][14][15]. With one exception, the results indicate that linoleic acid is the most prominent acid in Ipomoea seed oils followed by palmitic and oleic acids.…”
Section: Introductionmentioning
confidence: 77%
“…These data are summarized in Table 1. Fatty acid profile data for the seed oils of other members of the Convolvulaceae family also indicated that linoleic acid is the most common fatty acid in most of these oils (exception Merremia pentaphylla, with oleic acid second most common) [11,13].…”
Section: Introductionmentioning
confidence: 99%